Bhaktakabi Jagannātha Dāsa - Mahānti, Baṃśīdhara, 1924- (Oḍiśā Rājya Pāṭhyapustaka Praṇaẏana o Prakāśana Saṃsthā, 1977)
On the works of Jagannātha Dāsa, 1487-1547, medieval Oriya poet and Vaishnavite teacher; a study.